Enabling Effective Talent Management through a Macro-Contingent Approach: A Framework for Research and Practice. Issue 3 (July 2019) - King, Karin A.; Vaiman, Vlad
The forces and systems, which shape the available supply, composition and flow of talent into and out of organisations today have become increasingly complex and fluid. Most firms today extend their operations across regions and many compete globally, existing within one or more external contexts, known as macro talent management systems (MTM). Shaped by economic, political, regulatory, technological, and cultural conditions, MTM has the potential to directly or indirectly empower or disrupt organisational ability to attract, engage, and retain the talent crucial to achieving competitive business objectives. Yet organisations today may overlook the influence of external MTM systems to complement or constrain organisational talent management effectiveness, limiting the firm's ability to generate benefit and mitigate risk stemming from variance in macro talent contexts. Introducing a macro-contingent view of talent management, this paper identifies three pivotal shifts needed to enable effective talent management practice and proposes a framework for future research.